NuGrid stellar data set – II. Stellar yields from H to Bi for stellar models with MZAMS = 1–25 M⊙ and Z = 0.0001–0.02. Issue 1 (29th June 2018) - Ritter, C; Herwig, F; Jones, S; Pignatari, M; Fryer, C; Hirschi, R
ABSTRACT: We provide here a significant extension of the NuGrid Set 1 models in mass coverage and towards lower metallicity, adopting the same physics assumptions. The combined data set now includes the initial masses M_ZAMS/ M_ = 1, 1.65, 2, 3, 4, 5, 6, 7, 12, 15, 20, 25 for Z = 0.02, 0.01, 0.006, 0.001, 0.0001 with α-enhanced composition for the lowest three metallicities. These models are computed with the mesa stellar evolution code and are evolved up to the AGB, the white dwarf stage, or until core collapse. The nucleosynthesis was calculated for all isotopes in post-processing with the NuGrid mppnp code. Explosive nucleosynthesis is based on semi-analytic 1D shock models. Metallicity-dependent mass-loss, convective boundary mixing in low- and intermediate-mass models and H and He core burning massive star models are included. Convective O-C shell mergers in some stellar models lead to the strong production of odd-Z elements P, Cl, K, and Sc. In AGB models with hot dredge-up, the convective boundary mixing efficiency is reduced to accommodate for its energetic feedback. In both low-mass and massive star models at the lowest metallicity, H-ingestion events are observed and lead to i -process nucleosynthesis and substantial 15 N production. Complete yield data tables, derived data products and online analytic data access are provided.